2006
DOI: 10.1523/jneurosci.4218-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Induced Changes in Spinal Cord Pain Processing

Abstract: Pain is an essential sensory modality, signaling injury or threat of injury. Pain perception depends on both biological and psychological factors. However, it is not known whether psychological factors modify spinal mechanisms or if its effect is limited to cortical processing. Here, we use a placebo analgesic model to show that psychological factors affect human spinal nociceptive processes. Mechanical hyperalgesia (hypersensitivity) after an injury is attributable to sensitized sensory neurons in the spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 29 publications
7
74
0
5
Order By: Relevance
“…Consistent with behavioral studies (7,11,40), the results indicate that placebo treatment induces increases in endogenous opioid activity in -opioid-rich limbic and paralimbic regions, including PAG, NCF, DRN, OFC, amygdala, two dissociable regions of the anterior cingulate (rACC and pgACC), ventral aINS, and thalamus. All of these regions have shown a response to placebo or expectancy effects in pain or pharmacological administration of opioids.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with behavioral studies (7,11,40), the results indicate that placebo treatment induces increases in endogenous opioid activity in -opioid-rich limbic and paralimbic regions, including PAG, NCF, DRN, OFC, amygdala, two dissociable regions of the anterior cingulate (rACC and pgACC), ventral aINS, and thalamus. All of these regions have shown a response to placebo or expectancy effects in pain or pharmacological administration of opioids.…”
Section: Discussionsupporting
confidence: 80%
“…54,55 Additionally, the placebo effect is significantly lessened in patients with Alzheimer's disease with pre-frontal cortex involvement 56 and can be abolished with experimental disruption of the prefrontal cortex through transcranial magnetic stimulation. 57 Beyond a specific supraspinal mechanism, more recent imaging studies demonstrate spinal cord-related responses to placebo 58,59 and suggest that placebo may modulate pain throughout the continuum of the nervous system. Placebo-related hypoalgesia may be quite specific and localized to the expected site while not present in regions separate from the area of application.…”
Section: Physiological Mechanisms Of Placebo Responsesmentioning
confidence: 99%
“…The recent advances in the neurobiology of the placebo effect have shown that the administration of a placebo (inert substance), along with verbal suggestions of clinical benefit, activates different neurotransmitters in the brain, like endogenous opioids (Levine et al, 1978;Amanzio and Benedetti, 1999;Zubieta et al, 2005;Wager et al, 2007) and dopamine (de la Fuente-Fernandez et al, 2001;Strafella et al, 2006), and is associated to neural changes at both the cortical and subcortical level (Petrovic et al, 2002;Benedetti et al, 2004;Wager et al, 2004;Kong et al, 2006;Matre et al, 2006;Price et al, 2007). Powerful placebo responses can be obtained after pharmacological preconditioning, whereby the repeated administration of a drug is replaced with an inert substance (Ader and Cohen, 1982;Benedetti et al, 2005;Colloca and Benedetti, 2005;Pacheco-Lopez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%